Explicație pas cu pas:
9. a)[tex](-2)^{3} *(-2)^{2}=(-2)^{3+2}[/tex](conform regulii a^m*a^n=a^m+n);
b)[tex]3^{6} =3^{3}*3^{3}[/tex];
deoarece 3^3*3^2=3^3+2=3^5 ->3^5≠3^6 si
3^3*3^3=3^3+3=3^6 ->3^6=3^6;
c)[tex](-5)^{4}* (-5){2}+(-5)=(-5)^{7}[/tex]
deoarece (-5)=(-5)^1;
d)[tex]3^{2} +3^{3}=9+27[/tex] (regula folosita la inmultirea cu puteri nu se aplica si la adunarea cu puteri);
10.a)[tex](-3)^{3} *(-3)^{2}=(-3)^{3+2}=(-3)^{5}[/tex];
b)[tex](+7)*(+7)^3=(+7)^{1+3}=(+7)^4[/tex];
c)[tex](-5)*(-5)*(-5)^4=(-5)^{1+1+4}=(-5)^6[/tex];
d)[tex](-4)^{1} *(-4)^2*(-4)^3*(-4)^0=(-4)^{1+2+3+0}=(-4)^6[/tex];